Prognostic Value of Neutrophil-to-Lymphocyte Ratio in Stroke: A Systematic Review and Meta-Analysis - Li, Wenxia; Hou, Miaomiao; Ding, Zhibin; Liu, Xiaolei; Shao, Yuan; Li, Xinyi (Frontiers in Neurology, 2021)
Abstract Background: With the increase of morbidity and mortality in stroke patients, it is important to seek a biomarker to predict the prognosis of patients with stroke. This meta-analysis aims at clarify the relationship between the neutrophil-to-lymphocyte ratio (NLR) and the prognosis of stroke patients. Methods: This study was pre-registered in PROSPERO (CRD42020186544). We performed systematic research in PubMed, Web of Science and EMBASE databases for studies investigating the prognostic value of NLR. Odds ratios (ORs) with 95% confidence intervals (CIs) were extracted and analyzed by Review Manager 5.3 and Stata 12.0 software. Heterogeneity was estimated by using Cochran's Q test and I2 value. Sensitivity analyses and subgroup analyses were also performed to explore the potential sources of heterogeneity. Publication bias was assessed with funnel plots and assessed by Egger's tests. Results: Forty-one studies with 27,124 patients were included. In the overall analysis, elevated NLR was associated with increased mortality in acute ischemic stroke (AIS) patients (OR = 1.12, 95% CI = 1.07-1.16) and in acute hemorrhagic stroke (AHS) patients (OR = 1.23, 95% CI = 1.09-1.39), poorer outcomes in AIS patients (OR = 1.29, 95% CI = 1.16-1.44) and in AHS patients (OR = 1.11, 95% CI = 1.03-1.20). While in terms of hemorrhagic transformation (HT), higher NLR had deleterious effects on HT in AIS patients (OR = 1.15, 95% CI = 1.08-1.23). Conclusions: This study demonstrated that elevated NLR was significantly associated with poor prognosis of stroke patients. Higher NLR is associated with a 1.1- to 1.3- fold increased risk of poor outcomes of AIS/AHS patients. NLR could be helpful as a potential prognostic biomarker to guide clinical decision-making.